Clinical Application of Three-dimensional Printing and Extended Reality in Congenital Heart Disease - Lau, Ivan Wen Wen (Curtin University, 2023)
This PhD study investigates the clinical role of the two emerging techniques, which are 3D printing and virtual reality, to improve the visualisation and surgical planning of congenital heart disease. This research findings show that both of these technologies can enhance the users’ perception on the spatial relationship of the heart structures and defects, and therefore improving the management of congenital heart disease.